The Changing Landscape of Kapampangan Vocabularies: A Diachronic Analysis - Ariel T. Gutierrez (Research in Language)
The study examined the evolution of the Kapampangan language over time through the use of historical texts, dictionaries, and linguistic tools, such as interview guides and word lists. Data were taken from 62 informants in 31 towns in the Kapampangan-speaking region; the provinces of Pampanga, Tarlac, Nueva Ecija, Bulacan and Bataan were included in the study. Elders who were 60 years old and above, and young adults aged 17-30 years old were the main sources of information for the study. One criterion was that the participants must be native Kapampangans, meaning they were born, grew up, and currently live in the province where Kapampangan is spoken. It compared the collected data from the past to the present day. The study also examined the impact of industrial and technological advancements on language evolution. The study revealed that the Kapampangan language has been influenced by Tagalog due to its geographical proximity, and most of the younger generation has adopted this change, assimilating elements of Tagalog. In addition, social media and technological innovations have contributed to this trend.